Validity of an immersive virtual reality training system for orthognathic surgical education - Wan, Teng; Liu, Kai; Li, Biao; Wang, Xudong (Frontiers in Pediatrics, 2023)
Virtual reality (VR) has been proven an important supplement for surgical education in medical students. However, studies on immersive VR (iVR) simulation in orthognathic surgical education are limited. This study aimed to assess the validity of the iVR surgical training system for orthognathic surgery. Participants completed questionnaires at the end of the course to assess the validity of the training system. The questionnaires included questions on the experience of using the iVR system and surgical authenticity. Seven experienced surgeons and seven inexperienced students were recruited in this study to use our self-developed iVR training system for orthognathic surgery. The participants showed strong agreement to the fidelity of our training system (4.35 out of 5), including the virtual environment, instruments, anatomy structures, and surgical procedures. The participants also strongly agreed that the iVR technique was essential in imparting surgical education. However, most of the participants experienced some degree of dizziness or fatigue after 1 hour of using the system. The iVR training system is a new method for imparting education about orthognathic surgery. The iVR training system can act as a supplement and potential substitute of the traditional surgical training method.